Infratentorial Stereotactic Biopsy of Brainstem and Cerebellar Lesions - Jacek Furtak; Paulina Śledzińska; Marek G. Bebyn; Tadeusz Szylberg; Stanisław Krajewski; Marcin Birski; Marek Harat (Brain Sciences, 2021)
Stereotactic biopsy of posterior fossa lesions is often regarded as hazardous due to the critical structures in that area. Therefore, the aim of the study was to evaluate the diagnostic accuracy and safety of infratentorial stereotactic biopsy of brainstem or cerebellar lesions and its associations with other clinical, laboratory, and radiological parameters. From January 2000 to May 2021, 190 infratentorial stereotactic biopsies of posterior fossa tumors, including 108 biopsies of brainstem lesions, were performed. Moreover, 63 supratentorial biopsies of cerebral peduncle lesions were analyzed to compare the safety and efficacy of both approaches. Additionally, the presence of antibodies against Toxoplasma gondii and Epstein–Barr Virus (EBV) were documented in 67 and 66 patients, respectively, and magnetic resonance imaging (MRI) scans were evaluated in 114 patients. Only 4% of patients had minor complications and 1.5% had major complications, including one patient who died from intracranial bleeding. Nine (4.7%) biopsies were non-diagnostic. Isocitrate dehydrogenase 1 (IDH1) mutation, 1p/19q codeletion, and O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation status were assessed in 29 patients, and were non-diagnostic in only 3 (10.3%) cases. Patients with high-grade gliomas (HGG) were more frequently seropositive for T. gondii than individuals with low-grade gliomas (LGG; p < 0.001). A total of 27% of HGG and 41% of LGG were non-enhancing on MRI. The infratentorial approach is generally safe and reliable for biopsy of brainstem and cerebellar lesions. In our study, the safety and efficacy of supratentorial biopsy of the cerebral peduncle and infratentorial biopsy of lesions below the cerebral peduncle were comparably high. Moreover, patients with HGG were more frequently seropositive for T. gondii than patients with LGG, and the relationship between toxoplasmosis and gliomagenesis requires further investigation.